2015
DOI: 10.1002/jmri.24995
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of magnetic resonance elastography for the pancreas at 3T

Abstract: With the elastic belt, miscalculation of the pancreatic stiffness was reduced. MRE showed differences of stiffness between normal pancreas and pancreatic lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 16 publications
(19 reference statements)
3
28
2
Order By: Relevance
“…The reported stiffness values at 60Hz by Shi et al (22) are in the range reported in our study. Furthermore, Itoh et al (23) reported only 2D in-plane stiffness values with only one encoding direction which produces higher stiffness values compared to 3D stiffness values (9,14) reported in our study. Whereas, Dittmann et al (24) reported stiffness values of 1.45kPa at 40Hz compared to 1.2kPa at 60Hz in young volunteers in this study.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…The reported stiffness values at 60Hz by Shi et al (22) are in the range reported in our study. Furthermore, Itoh et al (23) reported only 2D in-plane stiffness values with only one encoding direction which produces higher stiffness values compared to 3D stiffness values (9,14) reported in our study. Whereas, Dittmann et al (24) reported stiffness values of 1.45kPa at 40Hz compared to 1.2kPa at 60Hz in young volunteers in this study.…”
Section: Discussioncontrasting
confidence: 62%
“…Earlier study by Shi et al (22) reported stiffness values at 40Hz and 60Hz using a soft passive driver to induce the vibrations. However, in the current study we have used 60Hz vibrations with a hard passive driver that was designed for liver studies as used by Itoh et al (23); and was able to generate required displacement field with good penetration in the pancreas and also have shorter wavelength when compared to 40Hz vibration. Furthermore, Dittmann et al (24) used pressurized pads powered by medical compressed to induce vibrations in the pancreas ranging from 3060Hz in increments of 10Hz.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another way to indirectly assess the degree of tissue stiffness is by elastography, which is the representation of images of the mechanical properties of objects (elasticity) when exposed to a force tending to deform (12). Elastography can be classified based on the physical measurement valued at: a) strain or deformation; and b) wave velocity distortion or shear wave velocity (SWV); or depending on the driving method used: a) by manual compression (using direct force by hand or cardiovascular pulsations); b) acoustic radiation force impulse (ARFI); and c) by mechanical impulse (e.g., Fibroscan ® ) (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Reports on pancreatic elastography by ARFI technique have been increasing over the past 3 years (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), having noted that currently it can only be used with a percutaneous ultrasound equipment and not by EUS. Yashima et al (19) presented the first study of diagnostic accuracy by ARFI between healthy volunteers and patients with chronic pancreatitis, taking standard magnetic resonance imaging (MRI), MR cholangiopancreatography (MRCP) and/or endoscopic retrograde cholangiopancreatography (ERCP) as a reference, and describing for SWV of 1.4 m/s sensitivity and specificity of 75% and 72%, respectively.…”
Section: Introductionmentioning
confidence: 99%